An analysis of the waste lagoon water level influence on the liq-uefaction resistance of the tailings dams - Petkovski L., Mitovski S. (Greek Committee on Large Dams, 2019)
The tailings dams, due to the enormous volume of the waste lagoon, are earth-fill structures with high-est potential hazard for the surrounding. However, the numerous reports of collapses of the tailings dams in the last three decades, all over the World, indicate that the structural (static and dynamic) safety and the liquefaction resistance was not controlled with the proper caution. In this research, the waste lagoon water level influence on the liquefaction resistance of the hydro tailings dams is investi-gated. This is the first measure to decrease the liquefaction potential of the complex heterogeneous geo-environment and to obtain the acceptable dynamic stability of the tailings dam. In this paper are presented results from the analysis of the dynamic response, the liquefaction assessment and the seis-mic resistance for different lagoon water levels of the hydro tailings dam Topolnica, of the mine Buchim, Radovish. This tailings dam, in the east part of Republic of North Macedonia, is formed by combination of downstream (in the first phase) and upstream (in the second phase) method of con-struction, with total height from the crest to the downstream toe of the dam of 141.2 m.